2016
DOI: 10.1016/j.hpb.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

A survey of European-African surgeons' management of common bile duct stones

Abstract: Indications for single-stage LCBDE are not standardized and do not appear well established across E-AHPBA members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…[7,9] In Europe-Africa survey, one-stage laparoscopic approach is being applied in 12% of patients. [8] American study shows that during 1998-2016, supporters of two-stage approach increase, but those of laparoscopic and open methods decrease. [9] Though the supporters of open method are few, this method is being justified in some countries due to its low costs and when laparoscopic and endoscopic approaches failure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[7,9] In Europe-Africa survey, one-stage laparoscopic approach is being applied in 12% of patients. [8] American study shows that during 1998-2016, supporters of two-stage approach increase, but those of laparoscopic and open methods decrease. [9] Though the supporters of open method are few, this method is being justified in some countries due to its low costs and when laparoscopic and endoscopic approaches failure.…”
Section: Discussionmentioning
confidence: 99%
“…Metanalysis by Feng Q and co-authors revealed that there were no significant differences between laparoscopic choledochotomy and transcystic interventions regarding stone clearance, general complications, operating time, however, better results were observed in transcystic group in terms of biliary complications, hospital stay and expenses. [14] Despite of its several advantages, transcystic management also has some disadvantages such as cannulation difficulty, transition to choledochotomy in large stones, [8,15] and lithotripsy. [16] Some authors consider the transcystic approach as risky in stones of larger than 20 mm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment options for cholecystocholedocholithiasis (CCL) include two-stage endoscopic retrograde cholangiopancreatography (ERCP) followed by laparoscopic cholecystectomy (LC) (i.e., ERCP+LC), one-stage laparoscopic common bile duct exploration (CBDE) and LC (i.e., LCBDE+LC), and laparotomic CBDE and cholecystectomy [ 1 , 2 ]. With the development of laparoscopic and endoscopic equipment and technology, open CBDE is now rarely applied in clinical practice [ 3 ].…”
Section: Introductionmentioning
confidence: 99%